Kedaulatan Udara Indonesia dan Upaya-Upaya Perlindungannya - Vera Wheni Setijawati Soemarwi (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2017)
Indonesia is an archipelagic state1, 13.466 registered islands, and has a lot of potential natural resources. Unfortunately, the number of registered islands in several departments has unclear data2. The impact of unclear data is causing a potential territorial conflict between Indonesia and neighboring countries due to inadequate protection. A defined territory is an essential element of an independent state3. Defining a border of land, sea, and outermost islands4 is important for Indonesia to define Indonesian air sovereignty. The main purpose of the article is helping the Indonesian government to maintain and keep the air space and the outermost islands especially on the sovereignty of the 92 outermost islands. The writer considers that through the maintenance of 92 outermost islands, Indonesia will have the extensive air space since the defining sea territory is 12 miles from the outermost islands. The other benefit is defining the exclusive economic zone “in which the coastal state has the right of conserving the natural resources”5 and continental shelf measure from 200 miles from the outermost islands. Therefore, Indonesia has the extensive right to conserve the natural resources. The article is written based on individual research. It explores the ICJ decision on Sipadan dan Ligitan case and suggest the government of Indonesia to protect the Indonesian territory and sovereignty. Loosing one centimeter of the borders means loosing the territorial sea, air, land, contiguous zones, exclusive economic zones and other potential economic resources.Keywords: Sovereignty of an Archipelagic State; Teritorial Integrity; Air Sovereignty.